Biogas Enterprise / Wan Muhammad Syukri Mohamad Thani ... [et al.] - Mohamad Thani, Wan Muhammad Syukri; Mat Saad, Ifrah Ruwaida; Kamaruddin, Noor Akma; Liudin, Mohd Lokman Noor; Azinan, Nabilah (2009)
Our business is pointing to establish the new gas product that are produce from anaerobic decomposition of such waste materials as domestic, industrial and agricultural sewage. This decomposition will carry out by methanogenic bacteria, this obligate anaerobe will produce methane which is the main component of biogas. This methane will be collected and packing and are ready to be used by the customer. The name of our product is Biogas. This name was taking according to the name of the process that we are used to produce these gases. This gas is cheaper from another brand of gas because this gas is a renewable energy and it will reduce the cost production. This gas is environmental friendly and do not contribute to the pollution. No plumbum was used inside this gas and we can improve our environmental quality especially air quality if this gas was widely used by local industry. We will market these gases for industrial purposes in Sabah especially Kota Kinabalu. We believe that this industry has a big potential to develop in Malaysia especially in Sabah because this technology will help us to low the uses of electricity and this industry also will help us to safe our earth. Our target to commence this business is in the 1st January 2011. We hope our market will be well developed in Sabah especially in Kota Kinabalu and we will expand this business in all state of Malaysia then exported it to all of the country in Asia. We are really hope that this business wills success and well acceptable in the market.